2012
DOI: 10.5604/17322693.991610
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in viral infections

Abstract: There are some premises suggesting that mast cells are involved in the mechanisms of anti-virus defense and in viral disease pathomechanisms. Mast cells are particularly numerous at the portals of infections and thus may have immediate and easy contact with the external environment and invading pathogens. These cells express receptors responsible for recognition of virus-derived PAMP molecules, mainly Toll-like receptors (TLR3, TLR7/8 and TLR9), but also RIG-I-like and NOD-like molecules. Furthermore, mast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These cells influence the regulation of body homeostasis by acting on wound healing, angiogenesis and vascular permeability as well as take part in the homeostasis of tissues and organs that undergo continuous growth and remodelling . Mast cells play a prominent role in the host response to invading pathogens, such as bacteria or viruses and participate in innate and acquired immune mechanisms .…”
Section: Mast Cell Characteristicsmentioning
confidence: 99%
“…These cells influence the regulation of body homeostasis by acting on wound healing, angiogenesis and vascular permeability as well as take part in the homeostasis of tissues and organs that undergo continuous growth and remodelling . Mast cells play a prominent role in the host response to invading pathogens, such as bacteria or viruses and participate in innate and acquired immune mechanisms .…”
Section: Mast Cell Characteristicsmentioning
confidence: 99%
“…Activation of mast cells and increased levels of urinary histamine, which is a major product of mast cells were observed in dengue patients and the levels correlated with disease severity [ 25 ]. Several data indicated that virus stimulated mast cells selectively produced and secreted a variety of mediators including chemokines, cytokines, lipid mediators, and granule associated products.…”
Section: Immune Activation Markers As Predictors Of Severe Dengue Dismentioning
confidence: 99%
“…Nowadays, more and more data indicate that mast cells are critical component of host defence against a variety of microorganisms, mainly bacteria [8] and viruses [9]. The role of these cells in protection against fungal infections is less understandable.…”
Section: Introductionmentioning
confidence: 99%